Estimating Trends of Sea-Level Fluctuations from Tide Gauge Data Analysis along Bangladesh Coast - Hoque, Abdul (Chittagong University Journal of Biological Sciences, 2024)
The present study tries to determine the nature and magnitudes of relative sea-level to estimate present and future trends of mean sea-level (MSL) changes based on historical tide gauge data of Cox's Bazaar, Charchanga, Hiron Point, Khepupara and Sadarghat stations of Bangladesh. Annual PSMSL tide gauge dataset of Cox's Bazaar station shows 2.72 mm/year sea-level rise while CPA provided 'Metric' dataset of Sadarghat station demonstrate 3.93 mm/year sea-level rise along Chittagong coast. Accordingly, the sea levels are supposed to be increased 10.54 cm, 24.11 cm and 37.69 cm than the 1988 MSL (213.70 cm) at Cox's Bazaar by the years 2050, 2100 and 2150, respectively. Moreover, based on long-term PSMSL tide dataset of Charchanga, Hiron Point and Khepupara stations, the estimated rise of sea-levels along the respective coasts are 8.15.mm/year, 3:56 mm/year and 18.66 mm/year, respectively. Finally, 7.4 :mm/year average rate of sea-level rise has been calculated from all the studied datasets under present study. However, disregarding the exceptionally high rate (18.66 m.m/year) at Khepupara station determined average rate of sea level rise along Bangladesh coast is 4.59 mm/year which seems to be consistent with the global average. Consequently, the predicted sea level along Bangladesh coast are approximately 22 cm, 45 cm and 68 cm above their average MSL (210.4 cm) in the years 2050, 2100 and 2150, respectively. The Chittagong Univ. J. B. Sci. 8(1&2): 75-86, 2013